Impact of customer citizenship behavior on corporate brand experience - Abdul Jamak, A.B.S. (Institute of Electrical and Electronics Engineers Inc., 2015)
The aim this paper is to investigate the impact of customer citizenship behavior on corporate brand experience in hypermarkets. The data were collected from 711 respondents of four hypermarkets located in five different states of Malaysia. Covariance-Based Structural Equation Modeling was used for the data analysis. Three dimensions of customer citizenship behavior namely helping behavior, feedback and tolerance were regressed on corporate brand experience. Findings reveal that customers' helping behavior and tolerance behavior has positive impact on corporate brand experience while customers' feedback has insignificant impact on corporate brand experience. This research is unique in its investigation as corporate brand experience as consequence of customer citizenship behavior has not been investigated in the past literature. Â© 2015 IEEE.